Taxonomic and functional approaches of trophic interactions between large herbivores and plant communities in a mountain ecosystem - Bison, Marjorie (UiT The Arctic University of Norway, 2015)
The papers and note of this thesis are not available in Munin: Paper I. Bison M. et al. Upscaling the niche variation hypothesis from the intra- to the inter-specific level. Available in Oecologia (2015) 179:835–842 Paper II. Bison M. et. al. Taxonomic and functional niches differentiation between two large herbivore species. (Manuscript) Paper III. Bison M. et al. The relative contribution of biomechanical and biochemical traits in plant selection by ungulates over the year. (Manuscript) Paper IV. Ancin Murguzur F.J., Smis A., Bison M. et al. Over the frontiers: a single NIRS calibration for sub-arctic and temperate ecosystems. (Manuscript) Note. Bison M. et al. Comparison between two methods for estimating diet quality in large herbivores: NIRS-derived fecal nitrogen vs dietary nitrogen from ingested plants. (Manuscript) Given the key role of large herbivores on species and functional plant diversity, we aimed at better understanding the relationship between herbivory and plant communities mainly at a fine-scale, in order to reconcile objectives of population management and plant conservation. For this purpose, we used both taxonomic and functional approaches, and studied interactions at the inter- and intra-specific levels. We combined information coming from three databases: (1) diet data from DNA-metabarcoding applied on chamois (Rupicapra rupicapra), roe deer (Capreolus capreolus) and mouflon (Ovis gmelini musimon) faeces from the Bauges Massif, (2) characteristics of plant communities (plant composition, biomass, phenology), (3) plant functional traits. Analyses of intra-specific variability of the three large herbivores allowed us to upscale the niche variation hypothesis (NVH) of Van Valen from the intra- to the inter-specific level, i.e. we observed a positive relationship between the species niche breadth and among-individual variation. Then, based on two chamois subpopulations living in pastures, one living in sympatry with the mouflon and the other living in allopatry, we revealed the absence of ...